2022
DOI: 10.1080/19490976.2021.2022997
|View full text |Cite
|
Sign up to set email alerts
|

AhR/IL-22 pathway as new target for the treatment of post-infectious irritable bowel syndrome symptoms

Abstract: Alterations in brain/gut/microbiota axis are linked to Irritable Bowel Syndrome (IBS) physiopathology. Upon gastrointestinal infection, chronic abdominal pain and anxio-depressive comorbidities may persist despite pathogen clearance leading to Post-Infectious IBS (PI-IBS). This study assesses the influence of tryptophan metabolism, and particularly the microbiota-induced AhR expression, on intestinal homeostasis disturbance following gastroenteritis resolution, and evaluates the efficacy of IL-22 cytokine vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 76 publications
5
36
0
Order By: Relevance
“…As previously reported, 43 infection with C rodentium induces CHS after pathogen clearance by increasing intracolonic pressure to colorectal distension in male mice (P , 0.05 at 60 mm Hg and P , 0.01 at 80 mm Hg) (Figs. 5A and B).…”
Section: P Distasonis F1-2 Alleviates Colonic Hypersensitivity But No...supporting
confidence: 81%
See 2 more Smart Citations
“…As previously reported, 43 infection with C rodentium induces CHS after pathogen clearance by increasing intracolonic pressure to colorectal distension in male mice (P , 0.05 at 60 mm Hg and P , 0.01 at 80 mm Hg) (Figs. 5A and B).…”
Section: P Distasonis F1-2 Alleviates Colonic Hypersensitivity But No...supporting
confidence: 81%
“…A "leaky gut" is a hallmark of the DSS-induced CHS model, and we previously demonstrated that intestinal barrier integrity is also impaired in both infectious and postinfectious phases of this model. 43 Of interest, no effect of the F1-2 strain on CHS was observed in the NMS model, in which we previously observed only a slight increase in colonic permeability, but to a much lesser extent than in the 2 previous models. 38 Because translocation of bacteria or their metabolites beyond the gastrointestinal tract is one of the hallmarks of the intestinal hyperpermeability, 60 we confirmed in our study that there is an increase of intracolonic bacteria, reveled by 16S RNAscope staining, in the DSS-treated mice but not in the sensitized NMS mice.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…hCAP18 synthetic cDNA optimized for L. lactis expression was cloned into a pSEC plasmid as described in 70 to create pSEC:hCAP18; this was then transformed in L. lactis NZ9000 to create the recombinant strain LL-pSEC:hCAP18, in which the induction of hCAP18 was nisin-dependent. hCAP18 synthetic cDNA optimized for expression in mice was cloned into the proBi-H1 plasmid to create proBi-H1:hCAP18; this plasmid vector contained the repA and repC origin of replication, the chloramphenicol resistance gene, and the expression cassette from pcDNA3 (Invitrogen) as published before 71 . The resulting vector was 3.7 kb long.…”
Section: Methodsmentioning
confidence: 99%
“…[5] The composition and abundance of the gut microbiota in patients with PI-IBS are significantly different, and the levels of short-chain fatty acids (SCFAs), which exhibit inhibitory activity against pathogenic bacteria, are also reduced due to inflammatory immune responses. [6] The complex microbiota of the human gut affects host health, both directly and indirectly. The host provides a growth environment for the gut microbiota, which participates in maintaining host homeostasis by regulating intestinal development, nutrient digestion, and immune status, as well as affecting brain activity through the enteric nervous system.…”
Section: Introductionmentioning
confidence: 99%